2022
DOI: 10.1051/0004-6361/202141861
|View full text |Cite
|
Sign up to set email alerts
|

Photoprocessing of H2S on dust grains

Abstract: Context. Sulfur is a biogenic element used as a tracer of the evolution of interstellar clouds to stellar systems. However, most of the expected sulfur in molecular clouds remains undetected. Sulfur disappears from the gas phase in two steps. The first depletion occurs during the translucent phase, reducing the gas-phase sulfur by 7–40 times, while the following freeze-out step occurs in molecular clouds, reducing it by another order of magnitude. This long-standing question awaits an explanation. Aims. The ai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 53 publications
3
30
0
Order By: Relevance
“…We first notice the presence of H 2 S in the gas phase at the most external positions where CH 3 OH is not detected. This is compatible with an early depletion of Sulphur atoms onto grain surfaces [7], before significant depletion of CO. Since reactions with CO are the main destruction path of N 2 H + [8], when CO depletion occurs, N 2 H + starts increasing its abundance.…”
Section: Analysis and Resultssupporting
confidence: 70%
“…We first notice the presence of H 2 S in the gas phase at the most external positions where CH 3 OH is not detected. This is compatible with an early depletion of Sulphur atoms onto grain surfaces [7], before significant depletion of CO. Since reactions with CO are the main destruction path of N 2 H + [8], when CO depletion occurs, N 2 H + starts increasing its abundance.…”
Section: Analysis and Resultssupporting
confidence: 70%
“…We highlight, however, that H 2 S is the most abundant sulfuretted species in comets (Bockelée-Morvan & Biver 2017), in agreement with our results. Cazaux et al (2022) find that, under efficient self-shielding conditions, H 2 S survives on the surface of grains as the ice below 100 K, and is largely depleted from the grains at 150 K. However, if no self-shielding is assumed, most H 2 S is transformed, under the influence of UV radiation, into S x sulfur chains. Our Nautilus model predicts that gaseous S 8 and that the surface of grains is the seventh and eighth major sulfur carrier.…”
Section: Discussionmentioning
confidence: 89%
“…According to these measurements, the abundances of the icy species could account for <5% of the total sulphur. It has been suggested that this socalled depleted sulphur may be locked as refractory material (in particular as S 8 , Shingledecker et al 2020;Cazaux et al 2022), claiming sulphur depletion of more than two orders of magnitude. Intense observational and theoretical work has been carried out in the last decade to constrain the value of sulphur depletion, and there is increasing evidence for a moderate factor of 1-20 of sulphur depletion in cold and warm clouds (Esplugues et al 2013(Esplugues et al , 2014Fuente et al 2019;Navarro-Almaida et al 2020Bulut et al 2021;Codella et al 2021).…”
Section: Deuterium Fractionation Evolutionmentioning
confidence: 99%
“…However, H 2 S has never been detected in interstellar ices, and its abundance has been estimated to be smaller than 5 × 10 −8 (/H) (Jiménez-Escobar & Muñoz Caro 2011). Other solid species have been proposed as possible sulphur reservoirs, such as OCS, SO 2 , H 2 S 2 , CS 2 , and S 8 (e.g., Palumbo et al 1997;Druard & Wakelam 2012;Laas & Caselli 2019;Shingledecker et al 2020;Cazaux et al 2022), OCS being the only S-bearing molecule unambiguously detected in ice mantles in the infrared (Geballe et al 1985;Palumbo et al 1995) along with, tentatively, SO 2 (Boogert et al 1997;Zasowski et al 2009).…”
Section: Introductionmentioning
confidence: 99%